Nutrient sensing and metabolic stress pathways in innate immunity. (26th July 2013) - Tsalikis, Jessica; Croitoru, David O.; Philpott, Dana J.; Girardin, Stephen E.
Summary: Cells monitor nutrient availability through several highly conserved pathways that include the mTOR signalling axis regulated by AKT/PI3K, HIF and AMPK, as well as the GCN2/eIF2α integrated stress response pathway that provides cellular adaptation to amino acid starvation. Recent evidence has identified a critical interplay between these nutrient sensing pathways and innate immunity to bacterial pathogens, viruses and parasites. These observations suggest that, in addition to the well‐characterized pro‐inflammatory signalling mediated by pattern recognition molecules, a metabolic stress programme contributes to shape the global response to pathogens.